WILL THE RIVER IRTYSH SURVIVE THE YEAR 2030? IMPACT OF LONG-TERM UNSUITABLE LAND USE AND WATER MANAGEMENT OF THE UPPER STRETCH OF THE RIVER CATCHMENT (NORTH KAZAKHSTAN) - Hrkal Z.; Gadalia A.; Rigaudiere P. (My University, 2006)
The Irtysh river basin all the way from river spring in China across Kazakhstan as far as the Russian part of Siberia is among the most ecologically endangered and affected regions on our planet. The study provides a summary of the historical reasons for anthropological interventions in this area, which began with the construction of plants of the military—industrial complexes in the forties of the last century during World War II. These plants have a major share in extreme high concentrations of heavy metals in surface as well in groundwaters locally. The Semipalatinsk nuclear polygon plays a specific role as a source of contamination of local waters. The release of top secret data enabled us to gain knowledge about serious problems related to high radioactivity of groundwaters, which should spread uncontrollably through a system of secondary fissures activated by nuclear blasts. Another serious problem in this region is the quantitative aspect of contamination. Model simulations of water balance indicate that large industrial development in the spring area in China and continuously increasing water consumption in Kazakhstan may lead to desiccation of the lower stretch of this large river in Siberia during the summer months of 2030.
Keywords: IRTYSH BASIN; WATER QUALITY; RADIOACTIVE CONTAMINATION; HEAVY METALS CONTAMINATION; WATER BALANCE